Measurement of temperature-dependent mechanical properties of magnetorheological fluids using a parallel disk shear stress testing device. (May 2017) - Wang, Daoming; Zi, Bin; Zeng, Yishan; Xie, Fangwei; Hou, Youfu
Mechanical properties are critical to the working performance of magnetorheological fluids (MRFs), especially in high temperature situations. This paper presents an experimental investigation to analyze the effects of temperature on mechanical properties of MRFs. First, a parallel disk method was implemented for the shear stress measurement of MRFs and the measurement principle was theoretically illustrated. Then, a detailed introduction to the MRF sample preparation and the testing device development was performed as well. In the study, five kinds of MRF samples with different material parameters were prepared and a shear stress testing device which possesses the temperature control function was developed and evaluated. After these, a series of measurements were conducted on the viscosity–temperature characteristic, shear stress–temperature characteristic and thermal stability of MRF samples. Measuring results indicated that the mechanical properties of MRFs were obviously dependent on temperature. The phenomenon mainly embodied in the reduction of off-field viscosity and shear stress with increasing temperature, as well as the performance degradation after undergoing a low–high–low temperature cycle or a high temperature treatment of more than 150 ℃.